2014
DOI: 10.1007/s11665-014-1176-4
|View full text |Cite
|
Sign up to set email alerts
|

Tension-Compression Asymmetry Under Superplastic Flow in Magnesium Alloys

Abstract: Superplastic magnesium alloys prepared by ingot metallurgy and powder metallurgy were processed and characterized. By performing uniaxial tension and compression tests of the extruded alloys along the longitudinal direction, it was found that both alloys were highly symmetric at low-strain rates within the superplastic regime. However, near the maximum strain rate within the superplastic regime, the symmetric flow disappeared. Specifically, the flow stress in early deformation under tension was slightly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The trend for these m-values is found to be similar to those obtained from the compression tests, provided in Table 1. Several studies have also reported that crystal orientation (texture) had a negligible effect on ow stress during superplastic deformation, which are observed at elevated temperature ranges and in low strain rate regimes [36][37][38] . When GBS occurs even at room temperature, the material, which had similar m-value in tension and compression testing, are assumed to show an isotropic ow stress behavior.…”
Section: Resultsmentioning
confidence: 98%
“…The trend for these m-values is found to be similar to those obtained from the compression tests, provided in Table 1. Several studies have also reported that crystal orientation (texture) had a negligible effect on ow stress during superplastic deformation, which are observed at elevated temperature ranges and in low strain rate regimes [36][37][38] . When GBS occurs even at room temperature, the material, which had similar m-value in tension and compression testing, are assumed to show an isotropic ow stress behavior.…”
Section: Resultsmentioning
confidence: 98%
“…For reference, the flow stress under tension along extrusion direction was slightly lower than that under compression along the same direction [16]. This is probably because, in superplastic magnesium alloys, the flow stress under tension becomes lower than that under compression near the maximum strain rate within the superplastic regime [23]. Texture characterization before and after superplastic deformation.…”
Section: Methodsmentioning
confidence: 99%